Miltefosine Efficacy on Leishmania Donovani Promastigote - Alshakir, Braa A.; H. Zghair, Khawla (Iraqi Journal of Science, 2023)
In the current study, different concentrations of miltefosine drug, which is the first effective and safe oral treatment for visceral leishmaniasis, was evaluated against L. donovani promastigotes in comparison with pentosam drug. Direct counting microscopic assay was used to find 50% inhibitory concentration (IC50) of miltefosine and pentostam against L. donovani promastigotes. The IC50 of miltefosine drug was 45.42μg/ml, 46.76μg/ml and 36.68μg/ml after 24 hr, 48hr and 72hr respectively, In comparison with IC 50 of pentostam drug was 75.39 μg/ml after 72hr. There were significant differences (P˂0.05) between IC50 values of miltefosine and pentostam drugs from first day to third day.